Epidemiological Research: Terms and Concepts - Miettinen, O. S. (Springer Netherlands : Imprint: Springer, 2011)
This book is by a single author - someone who, after medical school, has devoted half-a-century of full-time effort to ever better understand both clinical and community medicine and the research that is needed to produce the scientific knowledge-base of these. The book is organized so as to address in separate sections first the preparatory topics of medicine (clinical and epidemiological), science in general, and statistics (mathematical); then topics of epidemiological research proper; and, finally, topics of 'meta-epidemiological' clinical research. In those two main sections, a further grouping is based on the distraction between objects and methods of study. In this framework, the particular topics are addressed both descriptively and quasi-prescriptively, commonly with a number of explicatory annotations. This book is intended to serve and a handbook for whomever is, in whatever way, concerned with epidemiological or 'meta-epidemiological' clinical research. But besides, it is intended to serve as a textbook for the students in introductory courses on 'epidemiological' research - to which end there is a suggested hierarchy of the concepts that might reasonably be covered.